Delovanje Slovenske vojske v času epidemije covida-19 - Kremžar Kovač, Tanja (Sodobni vojaški izzivi, 2021)
The article presents the phenomenon of the COVID-19 epidemic in the Republic of Slovenia with focus on the activities of the Slovenian Armed Forces. It describes the response of the Slovenian Armed Forces to the epidemic, and the procedures and processes applied as part of its missions at home and in international operations and missions abroad. These activities provided additional support to the state and its citizens in dealing with the new virus. The emphasis is put on the procedures and processes of the Military Medical Unit aimed at monitoring the epidemiological situation. Additionally, the epidemic-related activities of the Slovenian Armed Forces and its medical units are compared to the activities of several other armed forces.
Keywords: covid-19; epidemic; epidemije; Military Medical Unit; Slovenian Armed Forces; Slovenska vojska; Vojaška zdravstvena enota